Evidence to shared genetic correlation of ischemic stroke and intracerebral hemorrhage and cardiovascular related traits. - Wei He; Jiajia Shi; Yiming Qian; Tao Fan; Xuehong Cai; Haochang Li; Peng Huang; Qin Shi (PLoS ONE)
Background Previous studies have demonstrated the genetic basis of stroke and also revealed their genetic correlation with some cardiovascular related diseases or traits at the entire genome, which, however, would not give the answer which regions may mainly account for the genetic overlap. This study aims to identify specific genetic loci that contribute to the shared genetic basis between ischemic stroke subtypes and common cardiovascular traits. Methods We used Local Analysis of [co]Variant Annotation (LAVA), a recent developed local genetic correlation method, to perform a system local genetic correlation analysis on GWAS summary data of two major subtypes of stroke, including any ischemic stroke (AIS) and intracerebral hemorrhage (ICH), and ten common cardiovascular related diseases or traits (CRTs). We further used colocalization analysis to explore potential shared causal genes in loci with significant local genetic correlation. In addition, we also performed Transcriptome-wide association (TWAS) analysis and fine-mapping for each phenotype to functionally annotate significant loci. Results LAVA analysis identified a total of 3 significant local genetic correlations (Bonferroni-adjusted P <  0.05) across 3 chromosomes between AIS and systolic blood pressure (SBP), AIS and hypertension (HT), and ICH and body mass index (BMI), among which locus 7.24 explicated to harbor a shared causal variant for AIS and SBP. TWIST1 in locus 7.24 was defined to be nominally associated with SBP, but not for AIS. Fine-mapping analysis also only identified TWIST1 a credible causal gene for BMI. Conclusions Our study revealed the local genetic correlations between two stroke subtypes and ten common CRTs. Gene-level analyses indicated that biological explanations underlying these identified local genetic correlations may existed elsewhere beyond a common pattern of genetic-gene expression regulation.